Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

a) \(16^{12}=4^{2\cdot12}=4^{24}\)
\(64^8=4^{4\cdot8}=4^{32}\)
=>\(64^8>16^{12}\)

\(5^{36}\)và \(11^{24}\)
Ta có :
\(5^{36}=\left(5^3\right)^{12}=125^{12}\)
\(11^{24}=\left(11^2\right)^{12}=121^{12}\)
Vi \(125>121\)nên \(5^{36}>11^{24}\)
\(3^{100}\)và \(2^{150}\)
Ta có :
\(3^{100}=\left(3^2\right)^{50}=9^{50}\)
\(2^{150}=\left(2^3\right)^{50}=8^{50}\)
Vì \(9>8\)nên \(3^{100}>2^{150}\)

a)\(27^{11}=3^{33}>3^{32}=81^8\)
b)\(2^{5000}=32^{1000}>25^{1000}=5^{2000}\)
c)\(5^{36}=125^{12}>121^{12}=11^{24}\)
d)\(3^2>2^3\Rightarrow3^{2n}>2^{3n}\)\(n\in\)N*
a) Ta có:
\(27^{11}=\left(3^3\right)^{11}=3^{33}\)
\(81^8=\left(3^4\right)^8=3^{32}\)
Vì 33>32 \(\Rightarrow\)333 > 332 hay 2711 > 818
b) Ta có :
25000 = \(\left(2^5\right)^{1000}=32^{1000}\)
\(5^{2000}=\left(5^2\right)^{1000}=25^{1000}\)
Vì 32 > 25 \(\Rightarrow\)32^1000 > 25^1000 hay 2^5000 > 5^2000
c) Ta có:
5^36 = 5^12.3 = (5^3)^12 = 125^12
11^24 = 11^12.2 = (11^2)^13 = 121^12
Vì 125>121 => 125^12>121^12 hay 5^36>11^24

a ) 27 11 và 81 8
Ta có :
27 11 = ( 3 3 ) 11 = 3 33
81 8 = ( 3 4 ) 8 = 3 32
Vì 3 33 > 3 32
=> 27 11 > 81 8
b ) 625 5 và 125 7
Ta có :
625 5 = ( 5 4 ) 5 = 5 20
125 7 = ( 5 3 ) 7 = 5 21
Ví 5 20 < 5 21
=> 625 5 < 125 7
c ) 5 36 và 11 24
Ta có
5 36 = ( 5 6 ) 6 = 15625 6
11 24 = ( 11 4 ) 6 = 14641 6
Vì 15625 6 < 14641 6
=> 5 36 > 1124
d ) 3 2n và 2 3n
Ta có :
3 2n = ( 3 2 ) n = 9 n
2 3n = ( 2 3 ) n = 8 n
Vì 9 n > 8 n
=> 3 2n > 2 3n
so sánh
\(27^{11}\)và \(81^8\)
\(625^5\)và \(125^7\)
\(5^{23}\)và \(6.5^{22}\)
\(7.2^{13}\)và \(2^{16}\)

a) 2711 = ( 32 ) 11 = 32.11 = 322
818 = ( 34 ) 8 = 34.8 = 332
Vì 22 < 32 nên 322 < 332 hay 2711 < 818
b) 6255 = ( 54 ) 5 = 54.5 = 520
1257 = ( 53 ) 7 = 53.7 = 521
Vì 20 < 21 nên 520 < 521 hay 6255 < 1257
c) 523 = 522 . 5
6 . 522 giữ nguyên
Vì 5 < 6 nên 523 < 6 . 522
d) 7 . 213 giữ nguyên
216 = 213 . 23 = 213 . 8
Vì 7 < 8 nên 7 . 213 < 216

Trả lời
\(A=\frac{7}{12}+\frac{5}{12}\div6-\frac{11}{36}\)
\(A=\frac{7}{12}+\frac{5}{12}\times\frac{1}{6}-\frac{11}{36}\)
\(A=\frac{7}{12}+\frac{5}{72}-\frac{11}{36}\)
\(A=\frac{25}{72}\)
\(B=12\frac{1}{3}-\frac{5}{7}\div\left(24-23\frac{5}{7}\right)\)
\(B=\frac{37}{3}-\frac{5}{7}\div\left(24-\frac{166}{7}\right)\)
\(B=\frac{37}{3}-\frac{5}{7}\div\frac{2}{7}\)
\(B=\frac{37}{3}-\frac{5}{7}\times\frac{7}{2}\)
\(B=\frac{37}{3}-\frac{5}{2}\)
\(B=\frac{59}{6}\)
Bài làm:
Ta có:
\(A=\frac{7}{12}+\frac{5}{12}\div6-\frac{11}{36}\)
\(A=\frac{7}{12}+\frac{5}{72}-\frac{11}{36}\)
\(A=\frac{42+5-22}{72}=\frac{25}{72}\)
và
\(B=12\frac{1}{3}-\frac{5}{7}\div\left(24-23\frac{5}{7}\right)\)
\(B=\frac{37}{3}-\frac{5}{7}\div\left(24-23-\frac{5}{7}\right)\)
\(B=\frac{37}{3}-\frac{5}{7}\div\left(1-\frac{5}{7}\right)\)
\(B=\frac{37}{3}-\frac{5}{7}+1\)
\(B=\frac{265}{21}\)

a) \(27^{11}=\left(3^3\right)^{11}=3^{33}\)
\(81^8=\left(3^4\right)^8=3^{24}\)
\(\Rightarrow27^{11}>81^8\)
b) \(5^{36}=\left(5^3\right)^{12}=125^{12}\)
\(11^{24}=\left(11^2\right)^{12}=121^{12}\)
\(\Rightarrow5^{36}>11^{24}\)
c) \(5^{23}=5\cdot5^{22}\)
Ta có: \(6>5;5^{22}=5^{22}\)
\(\Rightarrow5^{23}< 6\cdot5^{22}\)

a. Ta có : 27 ^11 = (3^3)^11= 3^33
81^8=(3^4)^8 = 3 ^32
=> 27^11>81^8
b. 625^5= (5^4)^5=5^20
125^7=(5^3)^7=5^21
=> 125^7>625^5
c. 5^36= (5^3)^12 =125^12
11^24=(11^2)^12= 121^12
=> 5^36>11^24
d. 3^2n = 9^n
2^3n= 8^n
=> 3^2n>2^3n
\(a,27^{11}\)và \(81^8\)
Ta có:
\(27^{11}=\left(3^3\right)^{11}=3^{33}\)
\(81^8=\left(3^4\right)^8=3^{32}\)
Vì \(3^{33}>3^{32}\Rightarrow27^{11}>81^8\)
\(b,625^5\)và \(125^7\)
Ta có:
\(625^5=\left(5^4\right)^5=5^{20}\)
\(125^7=\left(5^3\right)^7=5^{21}\)
Vì \(5^{20}< 5^{21}\Rightarrow625^5< 125^7\)

\(A=\frac{7}{12}+\frac{5}{12}:6-\frac{1}{36}\)
\(=\frac{7}{12}+\frac{5}{72}-\frac{11}{36}\)
\(=\frac{42}{72}+\frac{5}{72}-\frac{22}{72}\)
\(=\frac{25}{72}\)
a/ Ta có :
\(5^{36}=\left(5^3\right)^{12}=125^{12}\)
\(11^{24}=\left(11^2\right)^{12}=121^{12}\)
Vì \(125^{12}>121^{12}\Leftrightarrow5^{36}>11^{24}\)
b/ Ta có :
\(5^{23}< 6.5^{22}\)
a, \(5^{36}\) và \(11^{24}\)
Ta có:
\(5^{36}\) = \(\left(5^3\right)^{12}\)= \(125^{12}\)
Và \(11^{24}\) = \(\left(11^2\right)^{12}\)= \(121^{12}\)
vì \(125^{12}\)> \(121^{12}\)
Nên \(5^{36}\) > \(11^{24}\)
b, \(5^{23}\) và 6. \(5^{22}\)
Mà \(5^{23}\)= 5. \(5^{22}\)
=> 5. \(5^{22}\) < 6. \(5^{22}\)
Nên \(5^{23}\) < 6. \(5^{22}\)